2018
DOI: 10.1016/j.ijcard.2018.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of Type D personality for impaired endothelial function in patients with coronary artery disease

Abstract: Type D personality was associated with impaired endothelial function in men with CAD. This association was robust across time, independent from depressive symptoms, and supports the notion that Type D has an adverse effect on cardiovascular health in patients with CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 48 publications
1
21
0
1
Order By: Relevance
“…Our study investigated the association between Type D personality and anxiety and depression. Apart from these clinical psychological constructs, there exists a large body of research investigating whether Type D personality is related to worse health-related outcomes in the general population (Mols & Denollet, 2010) or in people with cardiovascular disease (Denollet et al, , 2018. Because most of these studies did not apply latent variable modeling and did not test for quadratic NA and SI effects, an interesting avenue for future research would be to do so in preregistered, highly powered direct replication projects.…”
Section: Discussionmentioning
confidence: 99%
“…Our study investigated the association between Type D personality and anxiety and depression. Apart from these clinical psychological constructs, there exists a large body of research investigating whether Type D personality is related to worse health-related outcomes in the general population (Mols & Denollet, 2010) or in people with cardiovascular disease (Denollet et al, , 2018. Because most of these studies did not apply latent variable modeling and did not test for quadratic NA and SI effects, an interesting avenue for future research would be to do so in preregistered, highly powered direct replication projects.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the proposed atherosclerotic processes, one study in healthy community dwelling individuals showed that Type D personality was unrelated to flow-mediated dilation (a non-invasive measurement of endothelial dysfunction, and indirect assessment of nitric oxide (NO) functioning), or diameter, of the brachial artery [ 60 ]. In patients with more advanced phases of endothelial dysfunction, i.e., with overt CHD, Type D personality was associated with reduced flow-mediated dilation [ 62 •], and thus impaired endothelial-dependent vasodilation.…”
Section: Type D and Pathophysiological Pathways Related To Cardiac Rimentioning
confidence: 99%
“…Endothelial dysfunction induces coronary abnormalities that are critical in cardiovascular stenosis because endothelial cells regulate vascular and inflammatory responses [2]. Specifically, type-D personality is associated with impaired endothelial dysfunction in patients with CAD [48]. The mechanism underlying the influence of type-D personality on endothelial dysfunction remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the influence of type-D personality on endothelial dysfunction remains unclear. However, type-D personality characterized by stress may be considered to indicate a high risk because stress is known to induce endothelial dysfunction [48].…”
Section: Discussionmentioning
confidence: 99%